2012
DOI: 10.4103/0019-557x.96978
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective pictorial health warnings on tobacco products: Lessons learnt from India

Abstract: Pictorial warnings are effective in promoting smoking cessation as shown by research in the developed countries. This study aims to determine perceptions of Indians about the effectiveness of pictorial health warnings on tobacco packs which existed from May 31, 2009, to December 1, 2011. A cross-sectional survey was undertaken in five states of India with 1897 participants (56% males; 54% tobacco users). More tobacco users expressed that the pictorial warnings are inadequate to convey the health impact of toba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…Thus, the mandated warnings do not serve the desired purpose since they are not properly understood. Findings of this study corroborate with those of an earlier study conducted in Mumbai by Oswal et al (2011) and study by Arora et al (2012) in five different states, which suggest that pictorial warnings that existed on tobacco packs are perceived to be ineffective by the Indian population 1617…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the mandated warnings do not serve the desired purpose since they are not properly understood. Findings of this study corroborate with those of an earlier study conducted in Mumbai by Oswal et al (2011) and study by Arora et al (2012) in five different states, which suggest that pictorial warnings that existed on tobacco packs are perceived to be ineffective by the Indian population 1617…”
Section: Discussionsupporting
confidence: 90%
“…Despite this precedent, the initial Indian warning depicting a symbolic image of a scorpion was considered ‘diluted’ 20 21. After criticism from the public health community, the Indian Ministry of Health announced a subsequent set of warnings, this time with graphic images of oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies show promise for smokeless tobacco pictorial warnings, there remains a paucity of evidence specific to LMICs, which have a different context of use. The limited existing evidence includes six observational studies in India that demonstrate the ineffectiveness of the 2009 smokeless tobacco health warning (scorpion),20 21 23 34–36 which has since been updated. Thus, there is little evidence to guide regulators on selecting content for smokeless tobacco health warnings in the two countries that bear the greatest burden of use.…”
Section: Introductionmentioning
confidence: 99%
“…Though the Group asserted that they were catering to public sentiment by decreasing the size of the warning labels, a 2012 survey conducted by the non-governmental organisation HRIDAY (Health Related Information Dissemination Amongst Youth) in four Indian regions showed that 99% of the respondents supported larger and more effective pictorial warnings included on all tobacco products, including bidis and smokeless tobacco 48 49. The MoHFW released the milder GHWLs for use on cigarette, bidi and smokeless tobacco packs (figure 1).…”
Section: Resultsmentioning
confidence: 99%